2018
DOI: 10.1186/s12889-018-5132-3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing GHG emissions while improving diet quality: exploring the potential of reduced meat, cheese and alcoholic and soft drinks consumption at specific moments during the day

Abstract: BackgroundThe typical Western diet is associated with high levels of greenhouse gas (GHG) emissions and with obesity and other diet-related diseases. This study aims to determine the impact of adjustments to the current diet at specific moments of food consumption, to lower GHG emissions and improve diet quality.MethodsFood consumption in the Netherlands was assessed by two non-consecutive 24-h recalls for adults aged 19–69 years (n = 2102). GHG emission of food consumption was evaluated with the use of life c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…Targeting those foods could lower environmental impact and benefit human health. This is in line with results from a modelling study in the Netherlands showing that reducing the consumption of soft and alcoholic drinks throughout the day leads to significantly lower dietary GHG emissions of people in the Netherlands, while also having health benefits [46]. In addition to this, our results suggest that reducing the consumption of non-alcoholic beverages, such as coffee and tea and fruit-and vegetable juice, during the day could decrease blue water use.…”
Section: Discussionsupporting
confidence: 91%
“…Targeting those foods could lower environmental impact and benefit human health. This is in line with results from a modelling study in the Netherlands showing that reducing the consumption of soft and alcoholic drinks throughout the day leads to significantly lower dietary GHG emissions of people in the Netherlands, while also having health benefits [46]. In addition to this, our results suggest that reducing the consumption of non-alcoholic beverages, such as coffee and tea and fruit-and vegetable juice, during the day could decrease blue water use.…”
Section: Discussionsupporting
confidence: 91%
“…Potential changers (n=1026) were individuals who reported trying dietary guidance and were estimated to be likely to agree that humans contribute to climate change. These individuals were 16% of the sample (95% CI [15][16][17]. All replacements were made in equal calorie amounts, as estimated from the National Nutrient Database for Standard Reference.…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, a different Dutch study found decreases in GHGE and some improvements in diet quality when reducing consumption of red and processed meat. 16 However, none of these individual studies considered environ mental impacts, diet quality, and diet cost in a substitution analysis. No individuallevel substitution studies have been done in the USA, the country with the second-highest level of GHGE.…”
Section: Introductionmentioning
confidence: 99%
“…The goal may also be to identify the most advantageous intake scenario (Berjia et al, 2014), or to provide a quantitative estimate of the overall health impact. RBA can include only health effects or be "expanded" to include non-health factors such as economy, sustainability and consumer preference (Ocké MC, Toxopeus IB, Geurts M, Mengelers MJB, Temme EHM, 2017; Juliana M. Ruzante, Grieger, Woodward, Lambertini, & Kowalcyk, 2017;Seves et al, 2016;Temme et al, 2013; van de Kamp, Seves, & Temme, 2018).…”
Section: Aligning the Risk-benefit Question And The Methodological Apmentioning
confidence: 99%